The influence of experiential marketing on customer loyalty of sawah coffee shops in Pematangsiantar City - Febriyanti Sinaga; Arief Budiman; Mira Nurfitriya (Enrichment : Journal of Management, 2023)
This study was analyzed using descriptive analysis and a quantitative approach. This study aims to determine the effect of experiential marketing on customer loyalty at Sawah Coffee Shop, Pematangsiantar City. This study uses two variables, namely experiential marketing as the independent variable (X) and customer loyalty as the dependent variable (Y). The sample in this study were 50 respondents who were customers of the Sawah Coffee Shop, Pematangsiantar City, using a questionnaire as a data collection tool. This study uses quantitative research using simple linear regression analysis method. Based on the test results of the coefficient of determination, the result is 0.691. This shows that experiential marketing has an effect of 69.1% on customer loyalty and the remaining 30.9% is influenced by other factors not examined by the author.